Nuclear pore complexes concentrate on Actin/LINC/Lamin nuclear lines in response to mechanical stress in a SUN1 dependent manner - Mark A. Smith; Elizabeth Blankman; Christopher C. Jensen; Laura M. Hoffman; Katharine S. Ullman; Mary C. Beckerle (Heliyon, 2022)
Formation of robust actomyosin stress fibers (SF) in response to cell stretch plays a key role in the transfer of information from the cytoplasm into the nucleus. Actin/LINC/Lamin (ALL) nuclear lines provide mechanical linkage between the actin cytoskeleton and the lamin nucleoskeleton across the nuclear envelope. To understand the establishment of ALL lines, we used live cell imaging of cells exposed to cyclic stretch. We discovered that nuclear pore complexes (NPCs) concentrate along ALL lines that are generated in response to uniaxial cyclic stretch. The ALL-associated NPCs display increased fluorescence intensity of nucleoporins Pom121, TPR and Nup153 relative to nucleoporins that are distal to the ALL lines. Here we test the hypothesis that a LINC complex component of ALL lines, SUN1 is involved in the integration of NPCs with ALL lines. We generated CRISPR SUN1 knockdown and knockout cell lines and show that SUN1 is essential for normal integration of NPCs to ALL lines. Loss or elimination of SUN1 significantly diminishes NPC/ALL line integration, demonstrating a key role for SUN1 in the recruitment or stabilization of NPCs to a discrete subdomain of the nuclear envelope at ALL lines. This work provides new insight into the mechanism by which cells respond to mechanical force through nuclear envelope remodeling.